2021
DOI: 10.1161/circulationaha.121.053547
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1α Is a Central Regulator of Leukocyte-Endothelial Adhesion in Myocardial Infarction and in Chronic Kidney Disease

Abstract: Background: Cardiovascular diseases (CVD) and chronic kidney disease (CKD) are highly prevalent, aggravate each other, and account for substantial mortality. Both conditions are characterized by activation of the innate immune system. The alarmin IL-1α is expressed in a variety of cell types promoting (sterile) systemic inflammation. The aim of the present study was to examine the role of IL-1α in mediating inflammation in the setting of acute myocardial infarction (AMI) and CKD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 39 publications
2
48
1
1
Order By: Relevance
“…The current study discovered that both VCAM‐1 and ICAM‐1 were positively linked with MACE risk. The potential explanation would be that: (1) elevated VCAM‐1 facilitated the adhesion of circulating leukocytes 23 ; meanwhile, VCAM‐1 might promote adhesion and infiltration of monocytes into the endothelium 24 ; these processes boosted the progression of cardiac diseases; therefore, VCAM‐1 could forecast elevated MACE risk in STEMI patients; (2) raised ICAM‐1 might foster fibrosis, vascular hypertrophy, macrophage infiltration, as well as reactive oxygen species production, resulting in the incidence of MACE 25 ; therefore, elevated ICAM‐1 also had the potency to predict higher MACE risk in STEMI patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study discovered that both VCAM‐1 and ICAM‐1 were positively linked with MACE risk. The potential explanation would be that: (1) elevated VCAM‐1 facilitated the adhesion of circulating leukocytes 23 ; meanwhile, VCAM‐1 might promote adhesion and infiltration of monocytes into the endothelium 24 ; these processes boosted the progression of cardiac diseases; therefore, VCAM‐1 could forecast elevated MACE risk in STEMI patients; (2) raised ICAM‐1 might foster fibrosis, vascular hypertrophy, macrophage infiltration, as well as reactive oxygen species production, resulting in the incidence of MACE 25 ; therefore, elevated ICAM‐1 also had the potency to predict higher MACE risk in STEMI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Possible arguments would be that: (1) regarding age, STEMI patients with age ≥65 years were more likely to suffer from myocardial infarction, heart failure, cardiac death, etc 26–28 29 ; (3) inflammation participated in the progression of cardiovascular diseases, and CRP could reflect inflammation status 23,30,31 ; (4) STEMI patients with the multivessel disease were susceptible to MACE 32 ; therefore, abovementioned factors independently predicted MACE risk in STEMI patients. A subsequent prediction model performed by nomogram provided a reference for predicting the MACE risk at 1, 2, and 3 years; meanwhile, the ROC curve analysis suggested that this multivariate prediction model performed by nomogram may assist in MACE prediction for STEMI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells produce NO via endothelial nitric oxide synthase (eNOS) in the vessel wall [ 63 ], which hence regulates blood pressure and blood flow and it also inhibits oxidation of LDL [ 18 , 64 ]. Endothelial cells adhere to circulating leukocytes via vascular cell adhesion molecule-1 (VCAM-1) on their cell surface [ 65 ]. Endothelial cells assimilate oxidized LDL via low-density lipoprotein receptor-1 (LOX-1), which is conducive to the development of atherosclerotic plaques [ 66 ].…”
Section: Mechanism Of Action Of Colchicine In Cardiovascular Disease Preventionmentioning
confidence: 99%
“…Recently published research by Schunk et al demonstrated that IL-1α represents a central regulator of leukocyte-endothelial adhesion in myocardial infarction and in chronic kidney disease, so inhibition of IL-1α may serve as a novel anti-inflammatory treatment strategy for this population. 46…”
Section: Epidemiology Of Cardiovascular Diseases In Chronic Kidney Di...mentioning
confidence: 99%